How to strengthen Primary Health Care services in Sri Lanka to meet future challengers? - Gunasena Sunil Senanayake; Madapathage Gayan Buddhika Senanayake; Thushara Ranasinghe; Neelamani S.R Hewageegana (College of Community Physicians of Sri Lanka, 2017)
Sri Lanka has achieved good health indicators despite being a lower middle income country. The main contributory factor for this success lies with the policy of 'free education' and provision of healthcare services free of charge to the people at the point of delivery. Despite the success, Sri Lanka is currently experiencing an epidemiological transition, where the burden of disease has shifted from communicable diseases to Non-Communicable Diseases. The objective of this paper is to discuss novel health system approaches to strengthen primary healthcare to meet upcoming health challengers for Sri Lanka. Four strategic approaches have been identified. First strategy is to adopt primary health care based life-course approach and task shifting of primary healthcare workers to combat Non-Communicable Diseases, while maintaining three tier health service model. Innovative public health interventions have to be developed and implemented through primodial, primary, secondary and tertiary prevention levels. Second method is to re-model and re-orient primary medical care units in the country. Special emphasis should be given to quality of care, human resource for health and laboratory and diagnostic facilities within these institutions. In this strategy it is proposed to establish a General Practitioner (GP) system with the support of central government and the provincial ministries of health and to link this system with preventive and curative primary healthcare services at divisional level. Third strategy is to establish referral and gate keeping system in the health sector to minimize the bypassing phenomenon, which has created high over-utilization of secondary and tertiary care hospitals, and under-utilization of primary healthcare services. Final strategy is to introduce electronic medical record systems with exchanging of records parallel to referral system. This is essential to minimize compartmentalization of treatment and to improve continuum of care. Strengthening primary healthcare with comprehensive community based family focused care is the solitary solution to address the emerging health issues of Sri Lanka. Health authorities should consider these first-hand approaches in their health master plans and try to re-orient the health services to achieve future health challengers.